Balancing competing needs in kidney transplantation: does an allocation system prioritizing children affect the renal transplant function?. (2nd November 2016) - Weitz, Marcus; Sazpinar, Onur; Schmidt, Maria; Neuhaus, Thomas J.; Maurer, Elisabeth; Kuehni, Claudia; Parvex, Paloma; Chehade, Hassib; Tschumi, Sibylle; Immer, Franz; Laube, Guido F.
Summary: Children often merit priority in access to deceased donor kidneys by organ‐sharing organizations. We report the impact of the new Swiss Organ Allocation System (SOAS) introduced in 2007, offering all kidney allografts from deceased donors <60 years preferentially to children. The retrospective cohort study included all paediatric transplant patients (<20 years of age) before ( n = 19) and after ( n = 32) the new SOAS (from 2001 to 2014). Estimated glomerular filtration rate (eGFR), urine protein‐to‐creatinine ratio (UPC), need for antihypertensive medication, waiting times to kidney transplantation (KTX), number of pre‐emptive transplantations and rejections, and the proportion of living donor transplants were considered as outcome parameters. Patients after the new SOAS had significantly better eGFRs 2 years after KTX (Mean Difference, MD = 25.7 ml/min/1.73 m 2, P = 0.025), lower UPC ratios (Median Difference, MeD = −14.5 g/mol, P = 0.004), decreased waiting times to KTX (MeD = −97 days, P = 0.021) and a higher proportion of pre‐emptive transplantations (Odds Ratio = 9.4, 95% CI = 1.1–80.3, P = 0.018), while the need for antihypertensive medication, number of rejections and living donor transplantations remained stable. The new SOAS is associated with improved short‐term clinical outcomes and more rapid access to KTX. Despite lacking long‐term research, the study results should encourage other policy makers to adopt the SOAS approach.